EDUKASI GIZI SEBAGAI UPAYA PENCEGAHAN BALITA STUNTING DI KELURAHAN MUJA MUJU TAHUN 2023 - A.M, James Roberto; Ilham, Muhammad; Anderson, Roger; Grace, Yohana (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
ABSTRACK Yesterday's Covid-19 pandemic caused an increased risk of stunting prevalence in toddlers. One of the efforts that can be made to prevent stunting is through continuous education. The purpose of this community service activity (PKM) is to increase the knowledge and attitudes of posyandu cadres regarding the message of balanced nutrition which is carried out through outreach to the community in Muja Muju Village, Yogyakarta City District. The method used in this PKM activity is through socialization by conveying education to the community with, 4 (four) pillars of balanced nutrition which includes 1) consumption of a variety of foods, 2) Clean and Healthy Behavior (PHBS), 3) weight monitoring , and 4) physical activity. Messages were given to 17 posyandu cadres from the Muja Muju Village. The educational results showed that there was an increase in the average knowledge score regarding balanced nutrition related to the prevention of stunting in toddlers from 77.52 ± 10.82 SD during the pre-test to 82.19 ± 9.93 SD during the posttest. In addition, the average attitude score also increased from 40.21 ± 6.67 SD to 44.48 ± 5.44 SD. Posyandu cadres are expected to become agents of change in stunting prevention behavior through educating parents of toddlers to prevent stunting.